2004
DOI: 10.1007/s11664-004-0287-3
|View full text |Cite
|
Sign up to set email alerts
|

The interfacial reaction between Sn-Zn-Ag-Ga-Al solders and metallized Cu substrates

Abstract: The interfacial interaction between the Sn-8.55Zn-0.5Ag-0.5Ga-0.1Al solder and three kinds of metallized substrates (Cu, Cu/Au, and Cu/Ni-P/Au) does not form the Cu-Sn intermetallic compound (IMC). Continuous Cu-Zn and discontinuous Ag-Zn interfacial IMC layers formed between the Cu and Sn-Zn-Ag-GaAl solder, while Cu-Zn and Au-Al-Zn IMCs formed on the Cu/Au substrate. Only the Au-Al-Zn IMC formed at the interface when the electroless Ni-P deposit was the diffusion barrier between Cu and the Au surface layer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 19 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…The latter changes are due to the formation of a Cu-Ga intermetallic [5].The observed behavior is explained by the fact that the Cu-Ga compound has a larger formation constant than the Cu-Zn intermetallic. This type of behavior has been observed for other intermetallics involving Ga(II) [6,7].…”
Section: Elimination Of Cu(ii)-zn(ii) Intermetallic Interferencessupporting
confidence: 75%
“…The latter changes are due to the formation of a Cu-Ga intermetallic [5].The observed behavior is explained by the fact that the Cu-Ga compound has a larger formation constant than the Cu-Zn intermetallic. This type of behavior has been observed for other intermetallics involving Ga(II) [6,7].…”
Section: Elimination Of Cu(ii)-zn(ii) Intermetallic Interferencessupporting
confidence: 75%
“…However, in this study, Au is identified in the Ag-Au-Cu-Zn compounds. The phenomenon may be ascribed to the presence of Zn in the Sn-based solder because Au can easily react with Zn [28][29][30]. In our previous study [31], AgZn 3 and AuZn 3 may coexist in Ag-Au-Cu-Zn phase with Cu dissolution by XRD diffraction pattern.…”
Section: Methodsmentioning
confidence: 85%
“…25 In addition, both Cu 5 Zn 8 and Ag 5 Zn 8 compounds are of the same space group: I43(217) with Pearson symbol CI52. 27 Therefore, Ag atoms diffused to the Cu 5 Zn 8 phase and could be incorporated into it. The atomic radii of Zn and Cu are 0.133 nm and 0.128 nm, respectively.…”
Section: Resultsmentioning
confidence: 99%